Adaptive Performance in Early Career Transitions The Role of Learning Goal Orientation A Systematic Literature Review - Ayu Ambarwati; Ilham Arief; Ardi Ardi; Khoe Yao Tung (Journal of Economics and Business UBS, 2026)
Adaptive performance is a critical competency for employees navigating rapidly changing organizational environments; however, its theoretical foundations during early career transitions, particularly in government settings, remain underdeveloped. Following the PRISMA 2020 guidelines, this systematic review aimed to identify, synthesize, and evaluate evidence on adaptive performance during early career transitions, with a focus on learning goal orientation as an antecedent, career adaptability as a mediating resource, and the contextual influences of identity threat and bureaucratic structures within the public sector. Searches of Scopus and Semantic Scholar using the search string (("Adaptive Performance" OR "Learning Goal Orientation") AND Career) identified 209 records. After removing 50 duplicate records and screening 159 unique records, 42 studies were included in the final synthesis. Four thematic clusters emerged: (1) learning goal orientation as a dispositional antecedent of adaptability and performance; (2) career construction and self-concept mechanisms; (3) identity threat as a contextual moderator during early career entry; and (4) structural and cultural characteristics of government careers. Learning goal orientation consistently demonstrated a positive association with adaptive performance, primarily through the mediating role of career adaptability. Adaptive performance during early career transitions in government contexts is a dynamic, multidimensional outcome shaped by individual motivation, career construction processes, social support, and institutional constraints. Future research should prioritize longitudinal research designs, cross-cultural validation in emerging economies, and evidence-based interventions aimed at strengthening learning goal orientation